A proposed library programs for the implementation of a self-circulation system in the University of the Philippines Diliman Libraries - Quindoza, Mark Lawrence R.; Dorado, Dan Anthony D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
Circulation of library materials is one of the most vital tasks in a library. In the case of the University of the Philippines Libraries, a big percentage of the work done by the librarians includes circulation work. Since most of the unit libraries in the university are undermanned, focusing on the circulation work leads to neglecting other library duties and programs. A proposed solution for this problem was the implementation of a self-circulation system where the users could borrow the materials on their own. This was implemented in the Ateneo de Manila University Rizal Library using a commercially available system and was found to be very user-friendly and efficient.
This study aims to know if a similar system would be feasible for UP Libraries. It also aims to determine the advantages and disadvantages and the possible policies that could be implemented using the system. The first three steps of the systems development life cycle: planning, analysis and design were used for the study. Included in the planning stage is the needs assessment for the system. Users of the six unit libraries, namely the College of Engineering Library, College of Science Library, College of Arts and Letters Library, College of Mass Communication Library, National College of Public Administration and Governance and College of Fine Arts Library were asked to evaluate on a five-point scale the programs and services being offered in their respective libraries. The head librarians of the mentioned libraries were also interviewed to determine their viewpoints on the issues. It was shown that even if the work in the circulation seems to be alright, there are programs and services in the library that needed to be improved. In the analysis stage, the current system was analyzed and a new entity relationship diagram was proposed. In the third stage, which is design, a proposed design for the system with the corresponding functionalities was produced after considering the comments of the respondents.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) Libraries; Library circulation and loans..